The effectivity of polysaccharide extracted from marine algae, Euchema cottonii, on the immune response of tilapia, Oreochromis niloticus - ., Indriasari; Mangindaan, Remy E.P.; Rumengan, Inneke F.M. (AQUATIC SCIENCE & MANAGEMENT, 2014)
Title (Bahasa Indonesia): Efektifitas polisakarida yang diekstrak dari alga, Euchema cottonii, terhadap respon imun ikan nila (Oreochromis niloticus)This study was aimed to test the effectiveness of polysaccharide extracts of algae, Eucheuma cottonii, in increasing the nonspecific immune response and to get an extract with best efficacy on the immune response of the tilapia, Oreochromis niloticus. The design used completely randomized design (CRD) using 4 treatments, 0 mg/kg of saline material (A), 10 mg/kg of E. cottonii extract (B), 10 mg/kg of Iota (C), and 100 cells/ml of formaline killed vaccine (FKV), Aeromonas hydrophilla, each of which were with 3 (three) replications. The fish were acclimated for 2 weeks, and then treated for 4 weeks. Test animals were vaccinated through intraperitoneal injection 2 times at one week interval as much as 0.2 ml FKV taken with disposable plastic 1 ml syringe. The vaccination was done injecting the bacteria, A. hydrophilla, previously killed in 0.4% formaldehyde FKV at the density of 109 cells / ml. Then the test fish were injected with the test material extract solution. E. cottonii as much as 0.2 ml / fish. Injection point was between the pelvic fins and the lateral line near the anus. The results showed that administration of the polysaccharide extracted from algae in tilapia gave significant effect on nonspecific immune response increment of the fish (total leukocytes and phagocytic activity). Penelitian ini bertujuan untuk menguji keefektifan ekstrak polysakarida alga laut, Eucheuma cottonii, dalam meningkatkan respons kebal non-spesifik dan untuk mendapatkan suatu ekstrak dengan kualitas terbaik terhadap respons kebal ikan nila, Oreochromis niloticus. Penelitian ini mengguna-kan rancangan acak lengkap (RAL) dengan 4 perlakuan dan 3 ulangan. Perlakuan yang digunakan adalah A = 0 mg.kg-1 untuk bahan uji saline; B = 10 mg.kg-1 ekstrak alga E. cottonii; C = 10 mg.kg-1 untuk iota; D = FKV A. hydrophilla 109 sel/ml. Ikan nila pertama-tama dipelihara dalam kolam (2 x 1 m) selama 2 minggu untuk proses aklimatisasi dan kemudian diberi perlakuan selama 4 minggu. Hewan uji divaksinasi dengan injeksi secara intraperitoneal (IP) dilakukan 2 kali dengan selang waktu seminggu sebanyak 0,2 ml FKV yang diambil dengan plastic syringe disposable 1 ml. Vaksinasi dilakukan dengan menginjeksikan bakteri A. hydrophilla yang telah dimatikan dengan formalin 0,4% FKV pada kepadatan 109 sel/ml. Kemudian ikan uji disuntik dengan bahan uji larutan ekstrak E. cottonii dengan dosis penyuntikan 0,2 ml larutan/ikan. Titik suntik diantara sirip perut dan lateral line dekat anus.Hasil penelitian menunjukkan pemberian polisakarida yang diekstrak dari alga pada ikan nila memberi pengaruh yang nyata terhadap peningkatan respon imun nonspesifik ikan (total leukosit dan aktivitas fagositosis).